Telemedicine in monitoring pediatric LT patients before and during COVID‐19 pandemic. (10th September 2021) - Musaoğlu, Mirac; Yuksel, Muhammed; Mizikoglu, Ozlem; Arikan, Cigdem
Abstract: Background: The delivery of healthcare services by telemedicine decreases costs of traveling for patients, is less time‐consuming, and most importantly permits the connection between highly skilled specialists and patients. However, whether the use of telemedicine (text messaging) for LT patients was affected by the COVID‐19 pandemic is unknown. Methods: We collected data (following consent from patients and parents) from 57 patients (33 male/24 female) with a median age of 47 (IQR: 9–91) months, whom we followed up with text messaging between September 2019 and September 2020, spanning the 6 months prior to COVID‐19 and during this period. Results: In total, 723 text message mediated consultations occurred during this period, henceforth simply referred to as "messages." Three hundred and twenty‐eight (45%) messages occurred during the 6 months up to the start of the pandemic. Following the COVID‐19 outbreak, the number of messages increased to 395 (55%). The three most common reasons of messaging were post‐liver‐LT follow‐up messages ( n = 215/723, 29.7%), consultations for drug use ( n = 157/723, 21.7%), and medication prescriptions ( n = 113/723, 15.6%). Protocol biopsy discussions ( n = 33/723, 4.6%) and fever ( n = 27/723, 3.7%) were among others (vaccination, rash, diarrhea, cough, fatigue, acne). During the COVID‐19 outbreak, only post‐LT follow‐up messages increased significantly to 132/395 (33%) from 83/328 (25%) ( p ‐value: .02). Conclusions: We found that the pandemic resulted in an increase in the total number of text message mediated consultations and specifically for the use of post‐LT follow‐up. Messaging was effective for post‐LT follow‐ups and all patients were at least satisfied.